2021
DOI: 10.3389/fcell.2021.722734
|View full text |Cite
|
Sign up to set email alerts
|

Costunolide-Induced Apoptosis via Promoting the Reactive Oxygen Species and Inhibiting AKT/GSK3β Pathway and Activating Autophagy in Gastric Cancer

Abstract: Objective: Costunolide (Cos) is a sesquiterpene lactone extracted from chicory. Although it possesses anti-tumor effects, the underlying molecular mechanism against gastric cancer cells remains unclear. This study aimed to explore the effect and potential mechanism of Cos on gastric cancer.Methods: The effect of Cos on HGC-27 and SNU-1 proliferation was detected by CCK-8 and clone formation assay. The changes in cell apoptosis were determined using Hoechst 33258 and tunel staining. The morphology of autophagy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…We speculate that the cardioprotective effect of Cos may be partly attributed to its anti‐apoptotic effect. Moreover, studies have shown that Cos suppresses apoptosis of tumour cells in various tumour models 20,47,48 . Mao et al have reported the anti‐apoptotic capability of Cos in LPS‐induced acute lung injury, 45 indicating the anti‐apoptotic potential of Cos in inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that the cardioprotective effect of Cos may be partly attributed to its anti‐apoptotic effect. Moreover, studies have shown that Cos suppresses apoptosis of tumour cells in various tumour models 20,47,48 . Mao et al have reported the anti‐apoptotic capability of Cos in LPS‐induced acute lung injury, 45 indicating the anti‐apoptotic potential of Cos in inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have shown that Cos suppresses apoptosis of tumour cells in various tumour models. 20,47,48 inhibit the interaction between TAK1 and TAB1. 42 In addition, IKKβ may be another target of Cos, given that Cos inhibits LPS-induced BV2 microglial inflammation by inhibiting the IKKβ/NF-κB signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which ROS induces cancer cell death are diverse, including apoptosis, cell cycle arrest, and autophagy [ 12 ]. CTL, an active compound derived from Saussurea lappa Clarke and/or Laurus nobilis L, has been reported to induce ROS generation in various cancer cells, such as breast, prostate, gastric, oral, and colon cancer cells, which leads to anti-cancer effects by promoting apoptosis or autophagy [ 21 , 44 , 45 , 46 , 47 , 48 ]. Our previous studies also demonstrated that CTL inhibits breast cancer cell growth and metastasis by causing ROS-induced cell cycle arrest at the G2/M phase and inhibiting TNFα-induced NF-κB activation in both in vitro and in vivo models [ 44 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Costunolide (CTL), a sesquiterpene lactone, is a natural product derived from the plants Saussurea lappa Clarke and Laurus nobilis L. (Lauraceae) [ 18 ]. Previous studies have shown that CTL can efficiently induce programmed cell death, such as apoptosis and autophagy, mainly through ROS- and AKT-mediated signaling pathways in various cancers [ 19 , 20 , 21 , 22 ]. Similarly, CTL exerts its anti-cancer activity on breast cancer cells by targeting several signaling cascades associated with cell cycle arrest and apoptosis [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…AKT is a Ser/Thr protein. When phosphorylated and activated at T308 and S473, AKT can activate GSK3β, Caspase-9, and BAD and participate in the regulation of tumor progression and the inflammatory response (25). GSK3β is a serine/threonine kinase and is widely distributed in eukaryotic cells.…”
Section: Discussionmentioning
confidence: 99%